Natural fiber-induced degradation in PLA-hemp biocomposites in the molten state. (October 2020) - Mazzanti, V.; Salzano de Luna, M.; Pariante, R.; Mollica, F.; Filippone, G.
Highlights: Short hemp fibers significantly accelerate hydrolysis of PLA in the molten state. The key role of the water brought into the composite by the fibers is highlighted. Fiber drying and alkaline pre-treatment mitigate fiber-induced PLA degradation. Pro-degradative action of natural fibers can be exploited to promote biodegradation. Abstract: The effect of small amounts (≤3 wt%) of short hemp fibers on stability of a poly(lactic acid) (PLA) in the molten state is investigated through time-resolved rheology. The decrease over time of the zero-frequency complex viscosity was correlated to severe hydrolytic degradation of the PLA matrix. A kinetic model that accounts for thermal degradation and hydrolysis was fitted to the experimental viscosity data. The significant fiber-induced hydrolysis is due to traces of residual water bound to the fibers inside the composites after the processing steps. A significant mitigation of the fiber-induced PLA hydrolysis can be obtained by carefully drying the hemp fibers before melt compounding and (to a lesser extent) by subjecting the fibers to an alkaline treatment. On the other hand, if the interest is a shorter persistence in the environment, natural fibers can be exploited to accelerate degradation of biocomposites.